Unchildish Childish Stories by A. P. Chekhov (Proceedings of Southern Federal University. Philology, 2019)
Elena N. Petukhova (St. Petersburg, Russian Federation)Chekhov’s stories about children should not be considered as childish. In these stories questions and problems which are typical of Chekhov’s works are raised. And these problems turn out to be even tragic because they concern the most unprotected people – children. Chekhov does not connect humane feeling which distinguishes children’s image with idealization and tender emotion, their images are not entered in stereotype “infant”. Childhood is described from different sides in Chekhov’s stories: it is child’s world itself with its happiness and misfortunes, it is also child’s world which contacts with the world of adults, adult world and children’s perception of adults, interrelations between children and parents marked by A.P. Chekhov with communicative failure which takes place because of adults. Opposition of something natural, clear to something burdened with prejudice, “rules” and stereotyped views on the world shows falsity and “abnormality of the norm” of world order, its unhappiness. It is “hard to be child” in such kind of the world. Chekhov does not affirm its total conformity to reality. Child’s perception is narrowed and superficial, but contact with it evidently shows distortion primary and elementary norms of human contacts and behavior. In a number of stories, starting with the earliest ones, A.P. Chekhov used the method of deprivation in which elements of Chekhov’s peculiar way of narration “in manner and tone of the hero” are obvious.Key words: Chekhov, children, adults, attitude, peace, perception of the world, suspension, norm.DOI 10.23683/1995-0640-2019-1-19-27